Lithic production in quarry-workshops of Antofagasta de la Sierra (Catamarca). A contribution to understand lithic record and their techno-typological diversity - Bobillo, Federico Miguel (2020)
Lithic record of the quarry-workshops is the product of multiple activities and physical actions developed during millennia of exploitation of lithic resources. These practices generated materialities with technical-typological attributes that are distinctive. The aim of this research was to know the different knowledge and technical procedures developed by artisans in quarries-workshops and their expression in material culture. In this framework, samplings and a technical-typological analysis of cores, flakes and knapping tools were developed. First, different types of cores were recorded. This are related to particular “ways of doing”. In second place, flakes with particular technical-typological attributes were documented. This are linked to the flakes-cores reductions or to blanks kanpping. Third, knapping tools show physical actions in order to create, and possibly use, different kinds of products. In conclusion, from this research it was possible to access a technological dimension of the activities of knapping activities in quarries-workshop. On the other hand, it was possible to register different “practical knowledge” and its expression in material culture.